The health workforce conundrum for burn care in Uttar Pradesh, India: a qualitative exploration - Vikash Ranjan Keshri; Samina Parveen; Seye Abimbola; Brijesh Mishra; Mohammed Fahad Khurram; Margie Peden; Robyn Norton; Jagnoor Jagnoor (Global Public Health, 2024)
Delivering specialised care for major burns requires a multidisciplinary health workforce. While health systems ‘hardware’ issues, such as shortages of the healthcare workforce and training gaps in burn care are widely acknowledged, there is limited evidence around the systems ‘software’ aspects, such as interest, power dynamics, and relationships that impact the healthcare workforce performance. This study explored challenges faced by the health workforce in burn care to identify issues affecting their performance. Qualitative in-depth interviews were conducted with a purposively selected sample (n = 31, 18 women and 13 men) of various cadres of the burn care health workforce in Uttar Pradesh, India. Inductive coding and thematic analysis identified three major themes. First, the dynamics within the multidisciplinary team where complex relations, power and normative hierarchy hampered performance. Second, the dynamics between health workers and patients due to the clinical and emotional challenges of dealing with burn injuries and multitasking. Third, dynamics between specialised burn units and broader health systems are narrated in challenges due to inadequate first response and delayed referral from primary care facilities. These findings indicate that burn care health workers in India face multiple challenges that need systemic intervention with a multipronged human resource for health framework.